Variants in mitochondrial amidoxime reducing component 1 and hydroxysteroid 17‐beta dehydrogenase 13 reduce severity of nonalcoholic fatty liver disease in children and suppress fibrotic pathways through distinct mechanisms. Issue 8 (11th April 2022) - Hudert, Christian A.; Adams, Leon A.; Alisi, Anna; Anstee, Quentin M.; Crudele, Annalisa; Draijer, Laura G.; ,; Furse, Samuel; Hengstler, Jan G.; Jenkins, Benjamin; Karnebeek, Kylie; Kelly, Deirdre A.; et al.
Abstract: Genome‐wide association studies in adults have identified variants in hydroxysteroid 17‐beta dehydrogenase 13 ( HSD17B13 ) and mitochondrial amidoxime reducing component 1 ( MTARC1 ) as protective against nonalcoholic fatty liver disease (NAFLD). We aimed to test their association with pediatric NAFLD liver histology and investigate their function using metabolomics. A total of 1450 children (729 with NAFLD, 399 with liver histology) were genotyped for rs72613567T>TA in HSD17B13, rs2642438G>A in MTARC1, and rs738409C>G in patatin‐like phospholipase domain‐containing protein 3 ( PNPLA3 ). Genotype–histology associations were tested using ordinal regression. Untargeted hepatic proteomics and plasma lipidomics were performed in a subset of children. We found rs72613567T>TA in HSD17B13 to be associated with lower odds of NAFLD diagnosis (odds ratio, 0.7; 95% confidence interval, 0.6–0.9) and a lower grade of portal inflammation ( p  < 0.001). rs2642438G>A in MTARC1 was associated with a lower grade of hepatic steatosis ( p  = 0.02). Proteomics found reduced expression of HSD17B13 in carriers of the protective ‐TA allele. MTARC1 levels were unaffected by genotype. Both variants were associated with down‐regulation of fibrogenic pathways. HSD17B13 perturbs plasma phosphatidylcholines and triglycerides. In silico modeling suggested p.Ala165Thr disrupts the stability and metal binding of MTARC1 . Conclusion: Both HSD17B13 and MTARC1 variants are associated with less severe pediatric NAFLD. These results provide further evidence for shared genetic mechanisms between pediatric and adult NAFLD. Abstract : Here, we found that a common variant in HSD17B13 reduced the risk of NAFLD diagnosis in children. Another common variant, in MTARC1, reduces the severity of steatosis on biopsy. The variant in HSD17B13 lowers protein expression, whilst the MTARC1 variant appears to act by affecting enzyme function.image